Examining Regulatory Focus in the Information Processing of Imagery and Analytical Advertisements - Roy, Rajat; Phau, Ian (Taylor & Francis, 2014)
The results of two experimental studies show that matching a promotion (prevention) focus with imagery (analytical) information in an advertisement results in higher advertising effectiveness, together with increased intention to purchase. Mediation analyses show that the impact of a regulatory focus—information matching in evaluation and purchase intention—is partially mediated by the fluency of processing. Matching is also found to increase message persuasiveness, and this effect is fully mediated by processing fluency. Furthermore, in response to imagery (analytical) information types, promotion (prevention)-focused subjects are found to engage imagery (analytical) processing styles to support their regulatory orientation.